From honors education to regular education: the motivation and role of honors teachers as linking pins in innovations - Pierre van Eijl; R. Weerheijm; A.Pilot (Journal of the European Honors Council, 2024)
This exploratory study is about the question of how teachers perceived how their experience with honors education have promoted innovations in their regular education. In this study, we interviewed teachers from four universities of applied sciences about this question. Interviews were conducted in 2019 and 2020, which resulted in 11 cases of innovation in regular programs inspired by experiences with honors education. A first part of this study showed how structural honors characteristics were important in this transfer structural characteristics (Van Eijl, Weerheijm & Pilot, 2023). The research question of the second part focusses on the role of the honors teacher in the innovations. The method of cross-case analysis was chosen. Based on an analysis of the interview data, the results were summarized and illustrated with quotes from the interviews. These innovations are at the level of a single module but also at the level of an entire undergraduate program. Experiences with honors education are frequently mentioned by the teachers as a motivation to work on the innovation of their regular education. These teachers rated the positive effect of honors education for their innovations in regular education as (very) stimulating. In these innovation, the teachers see themselves as "linking-pin", intrinsic motivated to actively transferring experiences from honors programs to innovations in regular programs. According to these teachers honors programs have an interesting innovation potential for regular programs.